Character Education Management in Early Childhood Education - Kuncoro, Irfan; Yuniar, Annisa Putri; Sungkar, Salma Adib; Romadan, Ade Imun (STAI Publisistik Thawalib Jakarta, 2025)
The importance of character education from an early age lies in its role in shaping children's personality, morality, and social behaviour as the foundation for holistic development. As the first formal educational institution, Early Childhood Education (ECE) plays a strategic role in instilling these values through various methods and family support. This study aims to analyse the effectiveness of character education management strategies in ECE and to identify the challenges faced in their implementation. The research employs a qualitative case study approach using interview techniques, active and passive observation, and documentation. Data were analysed through source and technique triangulation to ensure the validity and credibility of the research findings. The results show that PAUD-TK ABABILS Sukoharjo designed an Islamic education management strategy by integrating the national curriculum with Islamic character values, employing methods such as nature contemplation (tadabur alam) and experiential learning. The implementation of this strategy includes the development of a vision, learning modules, reinforcement of Islamic values, as well as the development of human resources and infrastructure. Challenges identified include limited teaching staff and diverse student backgrounds. Evaluation is conducted periodically through observations, parent questionnaires, and teacher performance assessments, involving all stakeholders. This evaluation process ensures the program's effectiveness and continuous improvement to foster children's moral and spiritual character from an early age in a holistic manner. Conclusion: An integrated Islamic education management strategy that involves multiple stakeholders is effective in fostering children's character development from an early age through careful planning, implementation, continuous evaluation, and enhancement of educational quality and stakeholder collaboration.